PENGARUH LIABILITAS DAN EKUITAS TERHADAP PROFITABILITAS PADA PT. PRIMARINDO ASIA INFRASTRUCTURE TBK - Safira Nurlita1; Aliah Pratiwi (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
This study aims to determine the effect of liabilities and equity on profitability. Indicators to measure profitability use Return on Equity (ROE), while liabilities use the ratio of short-term debt to equity (STDE) and shareholder equity using the ratio of prorietary ratio (PR). this research was conducted at PT. Primarindo Asia infrastructure, tbk. This type of research is associative research. The sampling technique used is a non probability sampling technique that is purposive sampling, with the sample used is for 8 years. The analysis technique used in this study is the classic assumption test and multiple regression analysis. Based on the results of the regression analysis shows short-term liabilities, and capital alone has no influence on profitability either partially or simultaneously